The Morphology, Standing Stock and Habitat Distribution of Several Bamboo Species in the Reok Sub-District, Manggarai Regency, East Nusa Tenggara Province, Indonesia - Apu, Orlando Calvin; Pramatana, Fadlan; Purnama, Maria M. E.; Pamona Silvia Sinaga (Department of Forest Resources Conservation and Ecotourism - IPB University, 2024)
Bamboo plays a vital role in preventing soil erosion and conserving water. In East Nusa Tenggara Province, many communities rely on bamboo species, making its cultivation a priority due to the region’s favorable biophysical conditions and available support from Non-Governmental Orgabization as facilitators. Approximately 387 villages have undergone assessment and socialization processes aimed at developing bamboo villages, including the Reok sub-district. One of the next steps in this process is conducting an inventory of bamboo standing stock in the area.This study aims to assess the species diversity and standing stock of bamboo in Reok sub-district. Research was carried out at 11 randomly selected sampling points across six villages, using the single circular plot method (radius of 17.9 m), with a total of 55 plots. Each plot was surveyed to identify and quantify clumps and culms, categorized by age (young, medium, and old). Four bamboo species were identified: Bambusa spinosa, Bambusa vulgaris, Gigantochloa atter, and Dendrocalamus asper. Gigantochloa atter was the most prevalent species, found at nearly all survey points, and had the highest number of clumps and culms. The estimated standing stock of bamboo in the Reok sub-district is 57,496 clumps, with a total of 3,692,890 culms. Gigantochloa atter accounted for the majority, with 35,526 clumps and 1,815,593 culms. This standing stock holds significant potential for further development, as bamboo is a key non-timber forest product (NTFP) in the region, with the potential to enhance the local economy.